NASKAH KUNO DAN PERKEMBANGAN ISLAM DI MALUKU Studi Kasus Kerajaan Hitu, Maluku Tengah Abad XVI-XIX M - Wuri Handoko (Berkala Arkeologi, 2015)
This study uses data codex to see the process of Islamization in the former Kingdom of Hitu . This study aimed to identify the forms of Islamization and the development of Islamic teachings and sects. Research methods with quantitative and qualitative approaches codex of data based identification and classification of the type and content of the manuscript. Methods of emphasizes quantitative comparison of the quantity and percentage of types of texts, while the qualitative approach to identify the contents of the script to see the development of the Islamic streams in the region. The results showed that the shape and model of Islamization propaganda approach and Sufism is the most dominant in addition to education and literacy teaching the Koran and Islamic law (fiqh). Additionally Islamization in the region of the Kingdom Hitu also growing recognition institutes, as well as the influence of the Shia tradition. Thus , the process of Islamization from the Quran literacy education, the introduction of Islamic Sufism and the congregation as well as the development of Islamic schools into the factors of growth and development of Islam in the region since the Kingdom Hitu in 16th-19th century AD.